Precursor for forming yttrium-containing or scandium-containing thin film, method for forming yttrium-containing or scandium-containing thin film using said precursor, and semiconductor element comprising said yttrium-containing or scandium-containing thin film
By introducing cyclopentadienyl and amidinyl ligands into the precursor for film formation, the chemical structure of the precursor is optimized, and the problems of high viscosity and low volatility in film formation in the prior art are solved, and high-quality films are achieved and the improvement of dielectric characteristics.
Patent Information
- Application Number
- CN202380048791.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-16
- Filing Date
- 2023-08-07
- Publication Date
- 2025-02-07
AI Technical Summary
When forming high dielectric films in the prior art, leakage current is prone to deterioration due to band gaps, and commonly used precursor materials have high viscosity and low volatility, making it difficult to meet the needs of film formation engineering.
A precursor for forming yttrium or scandium films has been developed. By including cyclopentadienyl and amidino ligands, the chemical structure of the precursor is optimized to make it appear in a low viscosity, high volatility, heat resistance and liquid in a room temperature. Or low melting point solid state characteristics.
The formation of high-quality films used in film formation engineering is achieved, which improves the dielectric properties and heat resistance of the film, reduces leakage current, and improves the convenience of the process.
Smart Images

Figure CN119403954A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a precursor for forming a thin film containing yttrium or scandium, a method for forming a thin film containing yttrium or scandium using the precursor, and a semiconductor component containing the thin film containing yttrium or scandium, and more particularly to a precursor for forming a thin film containing yttrium or scandium that can form a low viscosity, high heat resistance, and high volatility by means of a chemical structure containing an amidine ligand, thereby forming a high-quality thin film, a method for forming a thin film using the precursor, and a semiconductor component containing the thin film. Background Art
[0002] As the integration level of semiconductor components is improved due to the miniaturization of the line width, the space allowed for realizing the capacitor structure is limited by the line width. Therefore, the manufacturing method of semiconductor components for realizing the capacitor structure is also limited in the existing organic silicon dielectrics. In particular, when high dielectric films are used to replace organic silicon dielectrics, the leakage current will be greatly degraded due to the band gap.
[0003] As one of the solutions to the above-mentioned problems, a technology capable of forming a high-quality thin film is required, and for this purpose, it is necessary to optimize the precursor used when forming the thin film.
[0004] As an example of existing precursor optimization solutions, a variety of doping precursors that can improve dielectric constants and leakage current characteristics have been proposed, but the corresponding precursors are generally solid phases or low-volatility liquid phases, and in particular, their high viscosity may induce a variety of problems in the thin film deposition process. Therefore, in order to optimize the thin film forming precursor, improving the physical properties of the precursor, such as high volatility and low viscosity, is a very important issue.
[0005] To this end, various metal-containing precursors have been developed. For example, Korean Patent Publication No. 10-2019-0008427 discloses a lanthanum metal-containing precursor containing an azallyl ligand, and Korean Patent Publication No. 10-2021-0089015 discloses an yttrium metal-containing precursor containing a cyclopentadienyl ligand.
[0006] Through the known technology as described above, it can be confirmed that complexes containing cyclopentadienyl groups, cyclopentadienyl groups substituted or combined with other ligands have lower melting points and higher volatility than compounds containing β-diketone or bis(trimethylsilyl)amide, and are therefore more suitable for use as precursors in thin film formation processes.
[0007] For the reasons described above, in the known technologies such as Korean Registered Patent No. 10-1660052, Korean Publication Patent No. 10-2019-0109142, and 10-2021-0084297, a chemical structure in which a cyclopentadienyl group and an amidine group as ligands are combined as a precursor containing yttrium or lanthanum metals is proposed. The report points out that the precursor combined with the ligand as described above can improve the disadvantages of the existing precursor with low vapor pressure and high viscosity, and is suitable for use in thin film formation processes. Summary of the invention
[0008] An object of the present invention is to solve the problems existing in the prior art as described above and to provide a novel yttrium- or scandium-containing thin film-forming precursor that can exhibit chemical properties suitable for a thin film-forming precursor.
[0009] Another object of the present invention is to provide a precursor for forming a thin film containing yttrium or scandium which exhibits chemical properties of low viscosity, high heat resistance and high volatility and is in a liquid state or a solid state with a relatively low melting point at room temperature.
[0010] Another object of the present invention is to provide a method for forming a thin film using the precursor.
[0011] Another object of the present invention is to provide a semiconductor component comprising the thin film.
[0012] In order to achieve the above-mentioned object, the yttrium- or scandium-containing thin film-forming precursor of the present invention is characterized by including a compound represented by the following Chemical Formula 1.
[0013]
Chemical formula 1
[0014]
[0015] In the chemical formula, M is yttrium or scandium metal, R1 and R3 are each independently a C1-C5 straight chain, branched or cyclic alkyl or alkenyl group, R2 is a hydrogen atom or a C1-C4 straight chain, branched or cyclic alkyl or alkenyl group, R' is the same as or different from each other and is a hydrogen atom or a C1-C4 straight chain, branched or cyclic alkyl or alkenyl group, and n is an integer from 1 to 5.
[0016] In addition, the R2 may be a C2-C4 straight chain, branched chain or cyclic alkyl or alkenyl group.
[0017] In addition, the R1 and R3 may each independently be a C2-C5 straight chain, branched chain or cyclic alkyl or alkenyl group, and the R2 may be a C2-C4 straight chain, branched chain or cyclic alkyl or alkenyl group.
[0018] In addition, the R1 and R3 may be methyl groups.
[0019] In addition, the R2 may be an isopropyl group.
[0020] In addition, the R1 and R3 may each independently be a C1-C5 straight-chain alkyl or alkenyl group.
[0021] In addition, the R1 and R3 may each independently be a C1-C5 straight-chain alkyl or alkenyl group, and the R2 may be a C1-C4 straight-chain alkyl or alkenyl group.
[0022] Furthermore, the R1 and R3 may all be the same, and may be an alkyl group or an alkenyl group.
[0023] Furthermore, the R1 to R3 may all be the same, and may be an alkyl group or an alkenyl group.
[0024] Furthermore, the viscosity of the yttrium- or scandium-containing thin film-forming precursor is preferably 60 cP or less.
[0025] Furthermore, the melting point of the yttrium- or scandium-containing thin film-forming precursor is preferably 70° C. or less.
[0026] In addition, the thin film forming precursor may further contain a solvent, and the solvent may be C1-C 16 The thin film forming precursor may contain 1 to 99 wt % of the solvent relative to the total weight of the thin film forming precursor.
[0027] The method for forming a thin film containing yttrium or scandium of the present invention is characterized in that it includes a process of forming a thin film on a substrate using the thin film forming precursor, and the process of forming a thin film on a substrate includes a process of forming a precursor thin film by depositing the thin film forming precursor on the surface of the substrate and a process of reacting the precursor thin film with a reactive gas.
[0028] Furthermore, the step of forming a precursor thin film may include a step of vaporizing the thin film forming precursor and transferring the vaporized thin film forming precursor into a chamber.
[0029] In addition, the deposition can be performed by one of the following projects: spin-on dielectric (SOD) project, low temperature plasma (LTP) project, chemical vapor deposition (CVD) project, plasma chemical vapor deposition (PECVD) project, high density plasma chemical vapor deposition (HDPCVD) project, atomic layer deposition (ALD) project or plasma atomic layer deposition (PEALD) project.
[0030] Furthermore, the process of forming a thin film containing yttrium or scandium on a substrate may include a step of forming the thin film by supplying the thin film forming precursor to the substrate and applying plasma.
[0031] Furthermore, a semiconductor device of the present invention is characterized by including a thin film produced by the above-mentioned method for forming a thin film containing yttrium or scandium.
[0032] According to the precursor for forming an yttrium or scandium-containing thin film of the present invention, it contains cyclopentadienyl and amidine ligands, so the precursor compound has excellent structural stability and exhibits low viscosity, high volatility, heat resistance, and the characteristics of a liquid state at room temperature or a solid state with a low melting point, thereby exhibiting physical properties suitable for use in the yttrium or scandium-containing thin film formation process.
[0033] Furthermore, a thin film containing yttrium or scandium can be formed using the precursor, and a semiconductor component including the thin film containing yttrium or scandium produced by the thin film forming method can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The H NMR spectrum of bis(ethylcyclopentadienyl)(diethyl-acetamidine)yttrium ( 1 H NMR) analysis results.
[0035] Figure 2 It is the result of thermogravimetric analysis (TGA) of bis(ethylcyclopentadienyl)(diethyl-acetamidine)yttrium.
[0036] Figure 3 It is the result of differential scanning calorimetry (DSC) analysis of bis(ethylcyclopentadienyl)(diethyl-acetamidine)yttrium.
[0037] Figure 4 The H NMR spectrum of bis(ethylcyclopentadienyl)(diethyl-n-propionamidyl)yttrium ( 1 H NMR) analysis results.
[0038] Figure 5 This is the result of thermogravimetric analysis (TGA) of bis(ethylcyclopentadienyl)(diethyl-n-propionamidino)yttrium.
[0039] Figure 6 The H NMR spectrum of bis(ethylcyclopentadienyl)(di-n-propyl-acetamidine)yttrium ( 1 H NMR) analysis results.
[0040] Figure 7 It is the result of thermogravimetric analysis (TGA) of bis(ethylcyclopentadienyl)(di-n-propyl-acetamidine)yttrium.
[0041] Figure 8 The H NMR spectrum of bis(isopropylcyclopentadienyl)(diethyl-acetamidine)yttrium ( 1 H NMR) analysis results.
[0042] Fig. 9 The H NMR spectrum of bis(cyclopentadienyl)(diethyl-acetamidine)yttrium ( 1 HNMR) analysis results.
[0043] Fig.10 It is the result of thermogravimetric analysis (TGA) of bis(cyclopentadienyl)(diethyl-acetamidine)yttrium.
[0044] Fig.11 The H NMR spectrum of bis(cyclopentadienyl)(diethyl-n-propionamidyl)yttrium ( 1 HNMR) analysis results.
[0045] Fig.12 This is the result of thermogravimetric analysis (TGA) of bis(cyclopentadienyl)(diethyl-n-propionamidino)yttrium.
[0046] Fig.13 The H NMR spectrum of bis(cyclopentadienyl)(di-n-propyl-acetamidine)yttrium ( 1 HNMR) analysis results.
[0047] Fig.14 It is the result of thermogravimetric analysis (TGA) of bis(cyclopentadienyl)(di-n-propyl-acetamidine)yttrium.
[0048] Fig.15 The H NMR spectrum of bis(methylcyclopentadienyl)(diethyl-acetamidine)yttrium ( 1H NMR) analysis results.
[0049] Fig.16 It is the result of thermogravimetric analysis (TGA) of bis(methylcyclopentadienyl)(diethyl-acetamidine)yttrium.
[0050] Fig.17 The H NMR spectrum of bis(methylcyclopentadienyl)(diethyl-n-propionamidyl)yttrium ( 1 H NMR) analysis results.
[0051] Fig.18 This is the result of thermogravimetric analysis (TGA) of bis(methylcyclopentadienyl)(diethyl-n-propionamidino)yttrium.
[0052] Fig.19 The H NMR spectrum of bis(methylcyclopentadienyl)(di-n-propyl-acetamidine)yttrium ( 1 H NMR) analysis results.
[0053] Fig. 20 It is the result of thermogravimetric analysis (TGA) of bis(methylcyclopentadienyl)(di-n-propyl-acetamidine)yttrium.
[0054] Fig.21 This is the result of thermogravimetric analysis (TGA) of bis(methylcyclopentadienyl)(di-n-propyl-acetamidine) scandium.
[0055] Fig. 22 This is a graph that illustrates the change in film thickness (film deposition rate) according to the number of deposition cycles at different temperatures in a thin film formation process using bis(ethylcyclopentadienyl)(diethyl-n-propionamidino)yttrium and bis(ethylcyclopentadienyl)(diethyl-acetamidine)yttrium as precursors.
[0056] Fig.23 This is a graph showing the change in film deposition rate (ALDwindow) at different temperatures in a thin film formation process using bis(ethylcyclopentadienyl)(diethyl-n-propionamidino)yttrium and bis(ethylcyclopentadienyl)(diethyl-acetamidino)yttrium as precursors.
[0057] Fig.24 The results of X-ray diffraction (XRD) analysis according to temperature in a thin film formation process using bis(ethylcyclopentadienyl)(diethyl-n-propionamidino)yttrium as a precursor.
[0058] Fig.25 It is the result of X-ray electron spectroscopy (XPS) analysis of bis(ethylcyclopentadienyl)(diethyl-n-propionamidino)yttrium at 275°C. DETAILED DESCRIPTION
[0059] Next, the present invention will be described in more detail. The terms or words used in this specification and claims should not be interpreted in a general or dictionary sense, but should be interpreted based on the principle that the inventor can appropriately define the concept of the term in order to describe his invention in the best way, so as to conform to the meaning and concept of the technical idea of the present invention.
[0060] The yttrium- or scandium-containing thin film-forming precursor according to the present invention is characterized in that it contains a compound represented by the following Chemical Formula 1.
[0061]
Chemical formula 1
[0062]
[0063] In the chemical formula, M is yttrium (Y) or scandium (Sc), R1 and R3 are each independently a C1-C5 straight chain, branched or cyclic alkyl or alkenyl group, R2 is a hydrogen atom or a C1-C4 straight chain, branched or cyclic alkyl or alkenyl group, R' is the same as or different from each other and is a hydrogen atom or a C1-C4 straight chain, branched or cyclic alkyl or alkenyl group, and n is an integer from 1 to 5.
[0064] In the chemical formula 1, R1 and R3 constituting the amidine ligand may be the same or different, and may be constituted in various forms according to the desired effect to be achieved by the precursor provided by the present invention.
[0065] In addition, in the chemical formula 1, R2 constituting the amidine ligand may be a hydrogen atom or a C1-C4 linear, branched or cyclic alkyl or alkenyl group, and as a non-limiting example, may include n-alkyl groups such as ethyl, propyl and butyl.
[0066] The compound represented by Chemical Formula 1 is a precursor of a chemical structure having yttrium or scandium as a central metal atom and containing an amidine ligand, comprising a cyclopentadienyl ligand that can achieve properties such as a low melting point and high volatility, and also comprising a new amidine ligand that is different from the current ones, thereby being able to impart properties such as higher structural stability, low viscosity, high volatility, high heat resistance, and a liquid form at room temperature or a solid state with a low melting point.
[0067] That is, the precursor for forming a thin film containing yttrium or scandium according to the present invention has yttrium or scandium as the central metal and includes different types of ligands that can make different contributions to the performance improvement of the precursor, especially a new type of amidine ligand that can achieve excellent effects such as structural stability, low viscosity, high volatility, high heat resistance, and a liquid state at room temperature or a solid state with a low melting point, so that it can exhibit physical properties suitable for use in thin film formation engineering and thereby form a high-quality thin film.
[0068] The thin film forming precursor represented by the chemical formula 1 may have various forms with different functional groups.
[0069] In one embodiment, the R2 can be a straight chain, branched or cyclic alkyl or alkenyl group of C2-C4. When R2 is C2 or above, the intramolecular symmetry can be increased compared to the case of C1, thereby reducing the mutual interference between molecules, so that the precursor containing the ligand can be easily formed in a liquid state or a solid state with a lower melting point, and low viscosity characteristics can also be achieved.
[0070] In addition, the R1 and R3 may each independently be a C2-C5 straight chain, branched chain or cyclic alkyl or alkenyl group, and the R2 may be a C2-C4 straight chain, branched chain or cyclic alkyl or alkenyl group.
[0071] Furthermore, in one embodiment, the R1 and R3 may be methyl groups, and the R2 may be isopropyl groups.
[0072] In addition, the R1 and R3 may each independently be a C1-C5 straight-chain alkyl or alkenyl group.
[0073] Compared with branched or cyclic alkyl or alkenyl groups, straight chain alkyl or alkenyl groups can reduce the molecular weight by minimizing the structure of the ligand and thereby achieve the effect of improving volatility and vapor pressure.
[0074] Therefore, in the ligand according to one embodiment of the present invention, R1 and R3 can each be composed of a straight-chain alkyl group or an alkenyl group. In the above case, the vapor pressure of the thin film forming precursor containing the ligand can be increased, thereby achieving effects such as improving engineering convenience in the thin film forming process using the precursor.
[0075] In addition to the vapor pressure improvement effect, in the ligand in which R1 and R3 are each composed of a straight-chain alkyl group, the structural freedom of the ligand is high, so the freedom of the precursor applicable to the ligand can be improved. With the above effect, the interference between the precursors can be minimized, thereby achieving the effect of achieving the liquefaction and low viscosity characteristics of the precursor.
[0076] Therefore, in the amidine ligand according to one embodiment of the present invention, R1 and R3 in the chemical formula 1 can be composed of a straight-chain alkyl group or an alkenyl group. In the above case, the vapor pressure of the precursor containing the ligand can be increased, and it can be easily formed in a liquid state or a solid state with a lower melting point by increasing the degree of freedom, and low viscosity characteristics can also be achieved at the same time.
[0077] In addition, the R1 and R3 may each independently be a C1-C5 straight-chain alkyl or alkenyl group, and the R2 may be a C1-C4 straight-chain alkyl or alkenyl group.
[0078] Furthermore, the R1 and R3 may all be the same, and may be C1-C5 linear, branched or cyclic alkyl or alkenyl groups.
[0079] Furthermore, the R1 to R3 may all be the same, and may be C1-C4 linear, branched or cyclic alkyl or alkenyl groups.
[0080] An exemplary structure of the thin film forming precursor represented by Chemical Formula 1 as described above is as follows:
[0081]
[0082]
[0083]
[0084]
[0085] In addition, the cyclopentadienyl ligand may adopt a substituted structure, which can be used to adjust the size of the molecule and thereby adjust the viscosity and volatility of the compound.
[0086] The viscosity of the yttrium or scandium-containing thin film forming precursor is preferably 60 cP or less. In addition, the melting point of the thin film forming precursor is preferably 70° C. or less.
[0087] Due to the chemical structure of the thin film forming precursor of the present invention as described above, a liquid precursor with low viscosity, high heat resistance and high volatility can be obtained, thereby forming a high-quality thin film.
[0088] In addition, considering the conditions and efficiency of the thin film forming process, the thin film forming precursor of the present invention may further contain a solvent for dissolving or diluting the precursor compound. As the solvent, C1-C 16 One or a mixture of saturated or unsaturated hydrocarbons, ketones, ethers, glycol dimethyl ether, esters, tetrahydrofuran and tertiary amines. 16 Examples of saturated or unsaturated hydrocarbons include pentane, cyclohexane, ethylcyclohexane, heptane, octane and toluene, and examples of tertiary amines include dimethylethylamine and triethylamine.
[0089] In particular, the compound of the thin film forming precursor may be in a solid state at room temperature according to its chemical structure, and in the case as described above, the compound can be dissolved by including the solvent. That is, when the solvent is included, the solvent that can dissolve the precursor compound and the content thereof are preferably 1 to 99% by weight relative to the total weight of the thin film forming precursor.
[0090] Since the precursor containing or not containing the solvent can be gasified, it can be supplied into the chamber in the form of precursor gas. Therefore, depending on the type of the precursor compound for thin film formation, when it exists in a liquid state at room temperature and can be easily gasified, a thin film formation process can be performed without using a separate solvent.
[0091] In the case described above, the yttrium or scandium-containing thin film formation process can be performed by one of the following processes: spin-on dielectric (SOD) process, low temperature plasma (LTP) process, chemical vapor deposition (CVD) process, plasma chemical vapor deposition (PECVD) process, high density plasma chemical vapor deposition (HDPCVD) process, atomic layer deposition (ALD) process or plasma atomic layer deposition (PEALD) process.
[0092] For example, when the high-density plasma chemical vapor deposition (HDP-CVD) process is applied, it can be performed under high vacuum and high power compared to the atmospheric pressure chemical vapor deposition process (AP-CVD), low pressure chemical vapor deposition process (LP-CVD) or plasma enhanced chemical vapor deposition process (PE-CVD), so a thin film with a dense structure and excellent mechanical properties can be formed.
[0093] To this end, the thin film forming method according to the present invention includes a step of forming a thin film on a substrate using the thin film forming precursor.
[0094] Specifically, the process of forming a thin film containing yttrium or scandium on the substrate may include a process of forming a precursor thin film by depositing the thin film forming precursor on the surface of the substrate and a process of reacting the precursor thin film with a reactive gas.
[0095] Furthermore, the method may include a step of vaporizing the thin film forming precursor and transferring the vaporized thin film forming precursor into a chamber for deposition of the precursor.
[0096] In addition, the process of forming a thin film containing yttrium or scandium on the substrate may include a process of forming a thin film of metal, oxide, nitride, oxynitride, etc. by supplying the thin film forming precursor to the substrate and applying plasma in the presence of a reactive gas.
[0097] The film forming process can be performed under a chamber pressure condition of 0.1 to 10 Torr. In addition, the source power for forming plasma in the chamber is preferably 500 to 9,000 W, and the bias power is preferably 0 to 5,000 W. In addition, the bias power may not be applied according to specific circumstances.
[0098] In addition, the process of forming a thin film on a substrate is preferably performed at a temperature ranging from 150 to 500°C.
[0099] In addition, when supplying the thin film forming precursor, in order to further improve the electrical properties of the metal film finally formed, i.e., the electrostatic capacitance or the leakage current value, a second metal precursor can be introduced as needed. As the second metal precursor, a metal precursor containing one or more metals (M") selected from magnesium (Mg), strontium (Sr), barium (Ba), lanthanum elements (Ln), titanium (Ti), zirconium (Zr), hafnium (Hf), niobium (Nb), tantalum (Ta), aluminum (Al), indium (In), silicon (Si), germanium (Ge) and tin (Sn) atoms can be selectively further supplied. The second metal precursor can be an alkylamide compound or an alkoxy compound containing the metal. As an example, when the metal is Si, SiH(N(CH3)2)3, SiH2(N(C2H5)2)2, SiH2(NH t Bu)2、SiH3(N( i Pr)2), Si(OC4H9)4, Si(OC2H5)4, Si(OCH3)4 and Si(OC(CH3)3)4, etc.
[0100] The supply of the second metal precursor may be performed in the same manner as the supply method of the thin film forming precursor, the second metal precursor may be supplied together with the precursor onto the thin film forming substrate, or may be supplied sequentially after the supply of the precursor is completed.
[0101] In order to contact the thin film forming substrate, the thin film forming precursor and the optional second metal precursor as described above are preferably maintained at a temperature of 50 to 250° C., preferably 100 to 200° C. before being supplied into the reaction chamber.
[0102] In addition, after the precursor supply step and before the reactive gas is supplied, an engineering of purging an inert gas such as argon (Ar), nitrogen (N2) or helium (He) into the reactor can be performed to help the precursor and the optional second metal precursor move to the top of the substrate, or to form a pressure suitable for deposition in the reactor, and to discharge impurities and the like present in the chamber to the outside. At this time, it is preferable to make the pressure in the reactor reach 1 to 5 Torr by purging the inert gas.
[0103] In addition, as the reactive gas, one or a mixture of water vapor (H2O), oxygen (O2), ozone (O3), hydrogen peroxide (H2O2), hydrogen (H2), ammonia (NH3), nitric oxide (NO), nitrous oxide (N2O), nitrogen dioxide (NO2), hydrazine (N2H4) and silane (SiH4) can be used. When the process is carried out in the presence of an oxidizing gas such as water vapor, oxygen and ozone, a metal oxide film can be formed, and when the process is carried out in the presence of a reducing gas such as hydrogen, ammonia, hydrazine and silane, a metal monomer or a metal nitride film can be formed. In addition, a metal oxynitride film can be formed by mixing reactive gases.
[0104] In addition to the plasma treatment, a treatment process by heat treatment or light irradiation may be performed to provide thermal energy for depositing the thin film forming precursor, and the treatment process may be performed according to a general method. Preferably, in order to produce a thin film having a desired physical state and composition at a sufficient growth rate, the treatment process is performed at a substrate temperature of 100 to 1,000° C., preferably 250 to 600° C. in the reactor.
[0105] In addition, during the processing process, the process of purging an inert gas such as argon (Ar), nitrogen (N2) or helium (He) into the inside of the reactor as described above can also be performed to help the reactive gas move to the top of the substrate, or to form a pressure suitable for deposition in the reactor, and to discharge impurities or by-products present in the reactor to the outside.
[0106] The thin film can be formed by repeatedly performing the above-mentioned steps of charging the thin film forming precursor, charging the inert gas, charging the reactive gas, and charging the inert gas as one cycle or more.
[0107] Furthermore, by applying the thin film forming process, various semiconductor devices including thin films can be manufactured.
[0108] Next, the effects of the present invention will be described by way of examples.
[0109] [Synthesis Example 1] Synthesis of bis(ethylcyclopentadienyl)yttrium chloride [(EtCp)2YCl]
[0110] 204.9 ml (0.512 mol) of n-butyl lithium (n-BuLi) hexane solution (2.5 M) was slowly added to 300 ml of tetrahydrofuran (THF) and 48.22 g (0.512 mol) of ethylcyclopentadiene solution at -78 ° C and stirred for 30 minutes, and then stirred for 2 hours after heating to room temperature to produce a Li-EtCp solution. 50.0 g (0.256 mol) of yttrium chloride and 150 ml of toluene were added to a new flask and cooled to -78 ° C while stirring. The previously manufactured Li-EtCp solution was slowly added to the flask containing the yttrium chloride mixture and stirred at -78 ° C for 30 minutes, then heated to room temperature and stirred for 12 hours to synthesize bis (ethylcyclopentadienyl) yttrium chloride.
[0111] [Synthesis Example 2] Synthesis of bis(ethylcyclopentadienyl)(diethyl-acetamidine)yttrium [(EtCp)2Y(Et2Et-AMD)]
[0112] After adding 32.83g (0.256mol) of diethyl-acetamidine ester to 300ml of tetrahydrofuran (THF) and cooling to -78°C, 102.4ml (0.256mol) of n-butyl lithium (n-BuLi) hexane solution (2.5M) was slowly added dropwise to produce Li-(Et2Et-AMD). The solution was stirred at -78°C for 30 minutes and then heated to room temperature, followed by additional stirring at room temperature for 2 hours. The produced Li-(Et2Et-AMD) solution was slowly added dropwise to a flask containing (EtCp)2YCl at room temperature and stirred at room temperature for 12 hours. The mixture was evaporated under vacuum, then filtered after being dissolved in 250ml of pentane, and then the solvent and volatile substances were evaporated under vacuum. A light yellow liquid was obtained by treating the generated red liquid at 165°C and 40mTorr. The yield was 60.1 g (58.3%). The results of nuclear magnetic resonance (NMR, Bruker AV400MHz HD) analysis were as follows: Figure 1 shown.
[0113] 1 H NMR (C6D6, 25°C): 0.85 (t, 3H), 0.98 (t, 6H), 1.20 (t, 6H), 1.97 (q, 2H), 2.48 (q, 4H), 2.97 (q, 4H), 6.0 (dt, 8H).
[0114] The results of the analysis of the pale yellow liquid by thermogravimetric analysis (TGA, TA instrument company SDT Q600) at a nitrogen flow rate of 200 ml / min and a temperature rise rate of 10°C / min were 0%, with almost no residual mass. The results are shown as the thermogravimetric analysis (TGA) analysis results showing the weight loss percentage according to the temperature change. Figure 2 shown.
[0115] After the pale yellow liquid sample was placed in a sealed container for differential scanning calorimetry (DSC, Discovery 25 of TA Instrument Co., Ltd.) and maintained at 40°C for 10 minutes, a decomposition peak was observed at 431°C during the DSC analysis at a temperature increase rate of 10°C / min. The results are shown as DSC analysis results showing the change in thermal energy according to the temperature change. Figure 3 shown.
[0116] [Synthesis Example 3] Synthesis of bis(ethylcyclopentadienyl)(diethyl-n-propionamidyl)yttrium [(EtCp)2Y(Et2nPr-AMD)]
[0117] After adding 36.43g (0.256mol) of diethyl-n-propionamide to 300ml of tetrahydrofuran (THF) and cooling to -78°C, 102.4ml (0.256mol) of n-butyllithium (n-BuLi) hexane solution (2.5M) was slowly added dropwise to produce Li-(Et2nPr-AMD). The solution was stirred at -78°C for 30 minutes and then heated to room temperature, followed by additional stirring at room temperature for 2 hours. The produced Li-(Et2nPr-AMD) solution was slowly added dropwise to a flask containing Y(EtCp)2Cl at room temperature and stirred at room temperature for 12 hours. The mixture was evaporated under vacuum, then filtered after being dissolved in 250ml of pentane, and then the solvent and volatile substances were evaporated under vacuum. A light yellow liquid was obtained by distilling the generated red liquid at 185°C and 40mTorr. The yield was 65.1 g (61.0%). The results of nuclear magnetic resonance (NMR, Bruker AV400MHz HD) analysis were as follows: Figure 4 shown.
[0118] 1 H NMR (C6D6, 25°C): 0.83 (t, 3H), 0.99 (t, 6H), 1.20 (t, 6H), 1.36 (q, 2H), 1.98 (q, 2H), 2.50 (q, 4H), 3.00 (q, 4H), 6.0 (dt, 8H).
[0119] The results of the analysis of the pale yellow liquid by thermogravimetric analysis (TGA, TA instrument company SDT Q600) at a nitrogen flow rate of 200 ml / min and a temperature rise rate of 10°C / min were 0%, with almost no residual mass. The results are shown as the thermogravimetric analysis (TGA) analysis results showing the weight loss percentage according to the temperature change. Figure 5 shown.
[0120] [Synthesis Example 4] Synthesis of bis(ethylcyclopentadienyl)(di-n-propyl-acetamidine)yttrium [(EtCp)2Y(nPr2Et-AMD)]
[0121] After adding 40.02g (0.256mol) of diethyl-n-propionamidite to 300ml of tetrahydrofuran (THF) and cooling to -78°C, 102.4ml (0.256mol) of n-butyllithium (n-BuLi) hexane solution (2.5M) was slowly added dropwise to produce Li-(nPr2Et-AMD). The solution was stirred at -78°C for 30 minutes and then heated to room temperature, followed by additional stirring at room temperature for 2 hours. The produced Li-(nPr2Et-AMD) solution was slowly added dropwise to a flask containing Y(EtCp)2Cl at room temperature and stirred at room temperature for 12 hours. The mixture was evaporated under vacuum, then filtered after being dissolved in 250ml of pentane, and then the solvent and volatile substances were evaporated under vacuum. A yellow liquid was obtained by distilling the generated red liquid at 185°C and 40mTorr. The yield was 63.7 g (57.8%). The results of nuclear magnetic resonance (NMR, Bruker AV400MHz HD) analysis were as follows: Figure 6 shown.
[0122] 1 H NMR (C6D6, 25°C): 0.90 (m, 9H), 1.21 (t, 6H), 1.40 (q, 4H), 1.98 (q, 2H), 2.50 (q, 4H), 3.00 (q, 4H), 6.1 (dt, 8H).
[0123] The results of the analysis of the pale yellow liquid by thermogravimetric analysis (TGA, TA instrument company SDT Q600) at a nitrogen flow rate of 200 ml / min and a temperature rise rate of 10°C / min were 0%, with almost no residual mass. The results are shown as the thermogravimetric analysis (TGA) analysis results showing the weight loss percentage according to the temperature change. Figure 7 shown.
[0124] [Synthesis Example 5] Synthesis of bis(isopropylcyclopentadienyl)yttrium chloride [(iPrCp)2YCl]
[0125] 204.9 ml (0.512 mol) of n-butyl lithium (n-BuLi) hexane solution (2.5 M) was slowly added to 300 ml of tetrahydrofuran (THF) and 55.40 g (0.512 mol) of isopropylcyclopentadiene solution at -78 ° C and stirred for 30 minutes, and then stirred for 2 hours after heating to room temperature to produce a Li-EtCp solution. 50.0 g (0.256 mol) of yttrium chloride and 150 ml of toluene were added to a new flask and cooled to -78 ° C while stirring. The previously manufactured Li-EtCp solution was slowly added to the flask containing the yttrium chloride mixture and stirred at -78 ° C for 30 minutes, then heated to room temperature and stirred for 12 hours to synthesize bis (isopropylcyclopentadienyl) yttrium chloride.
[0126] [Synthesis Example 6] Synthesis of bis(isopropylcyclopentadienyl)(diethyl-acetamidine)yttrium [(iPrCp)2Y(Et2Et-AMD)]
[0127] After adding 32.83g (0.256mol) of diethyl-acetamidine ester to 300ml of tetrahydrofuran (THF) and cooling to -78°C, 102.4ml (0.256mol) of n-butyl lithium (n-BuLi) hexane solution (2.5M) was slowly added dropwise to produce Li-(Et2Et-AMD). The solution was stirred at -78°C for 30 minutes and then heated to room temperature, followed by additional stirring at room temperature for 2 hours. The produced Li-(Et2Et-AMD) solution was slowly added dropwise to a flask containing (iPrCp)2YCl at room temperature and stirred at room temperature for 12 hours. The mixture was evaporated under vacuum, then filtered after being dissolved in 250ml of pentane, and then the solvent and volatile substances were evaporated under vacuum. A yellow liquid was obtained by distilling the generated red liquid at 170°C and 20mTorr. The yield was 63.6 g (70.1%). The results of nuclear magnetic resonance (NMR, Bruker AV400MHz HD) analysis were as follows: Figure 8 shown.
[0128] 1 H NMR(C6D6,250C):0.85(t,3H),1.02(t,6H),1.24(d,12H),1.94(q,2H),2.82(m,2H),3.01(q,4H),6.01(dt,8H).
[0129] Thermogravimetric analysis (TGA, SDT Q600 from TA instrument) of the light yellow liquid was performed at a nitrogen flow rate of 200 ml / min and a temperature rise rate of 10°C / min. The result was 0%, indicating almost no residual mass.
[0130] [Synthesis Example 7] Synthesis of bis(cyclopentadienyl)yttrium chloride [(Cp)2YCl]
[0131] 204.9 ml (0.512 mol) of n-butyl lithium (n-BuLi) hexane solution (2.5 M) was slowly added to 300 ml of tetrahydrofuran (THF) and 33.85 g (0.512 mol) of cyclopentadiene solution at -78 ° C and stirred for 30 minutes, and then stirred for 2 hours after heating to room temperature to produce a Li-Cp solution. 50.0 g (0.256 mol) of yttrium chloride and 150 ml of toluene were added to a new flask and cooled to -78 ° C while stirring. The previously produced Li-Cp solution was slowly added to the flask containing the yttrium chloride mixture and stirred at -78 ° C for 30 minutes, then heated to room temperature and stirred for 12 hours to synthesize bis (cyclopentadienyl) yttrium chloride.
[0132] [Synthesis Example 8] Synthesis of bis(cyclopentadienyl)(diethyl-acetamidine)yttrium [(Cp)2Y(Et2Et-AMD)]
[0133] After adding 32.83g (0.256mol) of diethyl-acetamidine ester to 300ml of tetrahydrofuran (THF) and cooling to -78°C, 102.4ml (0.256mol) of n-butyl lithium (n-BuLi) hexane solution (2.5M) was slowly added dropwise to produce Li-(Et2Et-AMD). The solution was stirred at -78°C for 30 minutes and then heated to room temperature, followed by additional stirring at room temperature for 2 hours. The produced Li-(Et2Et-AMD) solution was slowly added dropwise to a flask containing (Cp)2YCl at room temperature and stirred at room temperature for 12 hours. The mixture was evaporated under vacuum, then filtered after being dissolved in 250ml of pentane, and then the solvent and volatile substances were evaporated under vacuum. A yellow solid was obtained by treating the generated red liquid at 166°C and 33mTorr. The yield was 51.2 g (48.5%). The results of nuclear magnetic resonance (NMR, Bruker AV400MHz HD) analysis were as follows: Fig. 9 shown.
[0134] 1H NMR (C6D6, 25°C): 0.81 (t, 3H), 0.96 (t, 6H), 1.90 (q, 2H), 2.96 (q, 4H), 6.16 (s, 8H).
[0135] The yellow solid was analyzed by thermogravimetric analysis (TGA, SDT Q600 of TA instrument company) at a nitrogen flow rate of 200 ml / min and a temperature rise rate of 10°C / min. The result was 1.5%, with almost no residual mass. The result is the thermogravimetric analysis (TGA) analysis result showing the weight loss percentage according to the temperature change. Fig.10 shown.
[0136] The yellow solid sample was placed in a sealed container for differential scanning calorimetry (DSC, Discovery 25 from TA instrument company) and maintained at 40°C for 10 minutes. During the DSC analysis, a decomposition peak was observed at 402°C after the temperature was increased at a rate of 10°C / min.
[0137] [Synthesis Example 9] Synthesis of bis(cyclopentadienyl)(diethyl-n-propionamidino)yttrium [(Cp)2Y(Et2nPr-AMD)]
[0138] After adding 36.433 g (0.256 mol) of diethyl-n-propionamide to 300 ml of tetrahydrofuran (THF) and cooling to -78°C, 102.4 ml (0.256 mol) of n-butyl lithium (n-BuLi) hexane solution (2.5 M) was slowly added dropwise to produce Li-(Et2nPr-AMD). The solution was stirred at -78°C for 30 minutes and then heated to room temperature, followed by additional stirring at room temperature for 2 hours. The produced Li-(Et2nPr-AMD) solution was slowly added dropwise to a flask containing (Cp)2YCl at room temperature and stirred at room temperature for 12 hours. The mixture was evaporated under vacuum, then filtered after being dissolved in 250 ml of pentane, and then the solvent and volatile substances were evaporated under vacuum. A red solid was obtained by treating the generated red liquid at 160°C and 28 mTorr. The yield was 49.6 g (53.8%). The results of nuclear magnetic resonance (NMR, Bruker AV400MHz HD) analysis were as follows: Fig.11 shown.
[0139] 1H NMR (C6D6, 25°C): 0.82 (t, 3H), 0.97 (t, 6H), 1.28 (t, 6H), 1.93 (q, 2H), 2.99 (q, 4H), 6.0 (s, 8H).
[0140] The result of the analysis of the red solid by thermogravimetric analysis (TGA, SDT Q600 of TA instrument company) at a nitrogen flow rate of 200 ml / min and a temperature rise rate of 10°C / min was 1.9%, with almost no residual mass. The results are shown as the thermogravimetric analysis (TGA) analysis results showing the weight loss percentage according to the temperature change. Fig.12 shown.
[0141] [Synthesis Example 10] Synthesis of bis(cyclopentadienyl)(di-n-propyl-acetamidine)yttrium [(Cp)2Y(nPr2Et-AMD)]
[0142] After adding 32.83g (0.256mol) of di-n-propyl-acetamidine ester to 300ml of tetrahydrofuran (THF) and cooling to -78°C, 102.4ml (0.256mol) of n-butyl lithium (n-BuLi) hexane solution (2.5M) was slowly added dropwise to produce Li-(nPr2Et-AMD). The solution was stirred at -78°C for 30 minutes and then heated to room temperature, followed by additional stirring at room temperature for 2 hours. The produced Li-(nPr2Et-AMD) solution was slowly added dropwise to a flask containing (Cp)2YCl at room temperature and stirred at room temperature for 12 hours. The mixture was evaporated under vacuum, then filtered after being dissolved in 250ml of pentane, and then the solvent and volatile substances were evaporated under vacuum. A yellow solid was obtained by treating the generated red liquid at 165°C and 36mTorr. The yield was 55.8 g (55.8%). The results of nuclear magnetic resonance (NMR, Bruker AV400MHz HD) analysis were as follows: Fig.13 shown.
[0143] 1 H NMR (C6D6, 25℃): 0.84(t,3H), 0.89(t,6H), 1.44(t,4H), 1.91(q,2H), 3.03(q,4H), 6.16(s,8H).
[0144] The yellow solid was analyzed by thermogravimetric analysis (TGA, TA instrument company SDT Q600) at a nitrogen flow rate of 200 ml / min and a temperature rise rate of 10°C / min. The result was 2.3%, with almost no residual mass. The results are shown as the thermogravimetric analysis (TGA) analysis results showing the weight loss percentage according to the temperature change. Fig.14 shown.
[0145] The yellow solid sample was placed in a sealed container for differential scanning calorimetry (DSC, Discovery 25 from TA Instrument Co., Ltd.) and maintained at 40°C for 10 minutes and then measured at a temperature increase rate of 10°C / min. During the differential scanning calorimetry (DSC) analysis, a decomposition peak was observed at 410°C.
[0146] [Synthesis Example 11] Synthesis of bis(methylcyclopentadienyl)yttrium chloride [(MeCp)2YCl]
[0147] 204.9 ml (0.512 mol) of n-butyl lithium (n-BuLi) hexane solution (2.5 M) was slowly added dropwise to 300 ml of tetrahydrofuran (THF) and 41.04 g (0.512 mol) of methylcyclopentadiene solution at -78°C and stirred for 30 minutes, and then stirred for 2 hours after heating to room temperature, thereby producing a Li-MeCp solution. 50.0 g (0.256 mol) of yttrium chloride and 150 ml of toluene were added to a new flask and then cooled to -78°C while stirring. The previously produced Li-MeCp solution was slowly added dropwise to the flask containing the yttrium chloride mixture and stirred at -78°C for 30 minutes, then heated to room temperature and stirred for 12 hours, thereby synthesizing bis (methylcyclopentadienyl) yttrium chloride.
[0148] [Synthesis Example 12] Synthesis of bis(methylcyclopentadienyl)(diethyl-acetamidine)yttrium [(MeCp)2Y(Et2Et-AMD)]
[0149] After adding 32.83g (0.256mol) of diethyl-acetamidine ester to 300ml of tetrahydrofuran (THF) and cooling to -78°C, 102.4ml (0.256mol) of n-butyl lithium (n-BuLi) hexane solution (2.5M) was slowly added dropwise to produce Li-(Et2Et-AMD). The solution was stirred at -78°C for 30 minutes and then heated to room temperature, followed by additional stirring at room temperature for 2 hours. The produced Li-(Et2Et-AMD) solution was slowly added dropwise to a flask containing (MeCp)2YCl at room temperature and stirred at room temperature for 12 hours. The mixture was evaporated under vacuum, then filtered after being dissolved in 250ml of pentane, and then the solvent and volatile substances were evaporated under vacuum. A colorless solid was obtained by treating the generated red liquid at 157°C and 62mTorr. The yield was 60.1 g (58.3%). The results of nuclear magnetic resonance (NMR, Bruker AV400MHz HD) analysis were as follows: Fig.15 shown.
[0150] 1 H NMR (C6D6, 25°C): 0.85 (t, 3H), 0.97 (t, 6H), 1.95 (q, 2H), 2.10 (s, 6H), 2.97 (q, 4H), 6.0 (dt, 8H).
[0151] The yellow liquid was analyzed by thermogravimetric analysis (TGA, TA instrument company SDT Q600) at a nitrogen flow rate of 200 ml / min and a temperature rise rate of 10°C / min. The result was 1.1%, with almost no residual mass. The results are shown as the thermogravimetric analysis (TGA) analysis results showing the weight loss percentage according to the temperature change. Fig.16 shown.
[0152] The yellow solid sample was placed in a sealed container for differential scanning calorimetry (DSC, Discovery 25 from TA instrument company) and maintained at 40°C for 10 minutes and then measured at a temperature increase rate of 10°C / min. During the differential scanning calorimetry (DSC) analysis, a decomposition peak was observed at 400°C.
[0153] [Synthesis Example 13] Synthesis of bis(methylcyclopentadienyl)(diethyl-n-propionamidino)yttrium [(MeCp)2Y(Et2nPr-AMD)]
[0154] After adding 36.43g (0.256mol) of diethyl-n-propionamide to 300ml of tetrahydrofuran (THF) and cooling to -78°C, 102.4ml (0.256mol) of n-butyllithium (n-BuLi) hexane solution (2.5M) was slowly added dropwise to produce Li-(Et2nPr-AMD). The solution was stirred at -78°C for 30 minutes and then heated to room temperature, followed by additional stirring at room temperature for 2 hours. The produced Li-(Et2nPr-AMD) solution was slowly added dropwise to a flask containing (MeCp)2YCl at room temperature and stirred at room temperature for 12 hours. The mixture was evaporated under vacuum, then filtered after being dissolved in 250ml of pentane, and then the solvent and volatile substances were evaporated under vacuum. A colorless liquid was obtained by treating the generated red liquid at 170°C and 67mTorr. The yield was 59.11 g (59.4%). The results of nuclear magnetic resonance (NMR, Bruker AV400MHz HD) analysis were as follows: Fig.17 shown.
[0155] 1 H NMR (C6D6, 25°C): 0.83 (t, 3H), 0.98 (t, 6H), 1.34 (t, 2H), 1.96 (q, 2H), 2.11 (s, 6H), 2.97 (q, 4H), 6.0 (dt, 8H).
[0156] The result of analyzing the colorless liquid by thermogravimetric analysis (TGA, SDT Q600 of TA instrument company) at a nitrogen flow rate of 200 ml / min and a temperature rise rate of 10°C / min was 0.9%, with almost no residual mass. The result is the thermogravimetric analysis (TGA) analysis result showing the weight loss percentage according to the temperature change. Fig.18 shown.
[0157] A colorless liquid sample was placed in a sealed container for differential scanning calorimetry (DSC, Discovery 25 from TA instrument company) and maintained at 40°C for 10 minutes and then measured at a temperature increase rate of 10°C / min. During the differential scanning calorimetry (DSC) analysis, a decomposition peak was observed at 410°C.
[0158] [Synthesis Example 14] Synthesis of bis(methylcyclopentadienyl)(di-n-propyl-acetamidine)yttrium [(MeCp)2Y(nPr2Et-AMD)]
[0159] [After adding 40.02 g (0.256 mol) of di-n-propyl-acetamidine ester to 300 ml of tetrahydrofuran (THF) and cooling to -78°C, 102.4 ml (0.256 mol) of n-butyl lithium (n-BuLi) hexane solution (2.5 M) was slowly added dropwise to produce Li-(nPr2Et-AMD). The solution was stirred at -78°C for 30 minutes and then heated to room temperature, followed by additional stirring at room temperature for 2 hours. The produced Li-(nPr2Et-AMD) solution was slowly added dropwise to a flask containing (MeCp)2YCl at room temperature and stirred at room temperature for 12 hours. The mixture was evaporated under vacuum, then filtered after being dissolved in 250 ml of pentane, and then the solvent and volatile substances were evaporated under vacuum. A yellow liquid was obtained by treating the generated red liquid at 155°C and 113 mTorr. The yield was 60.1 g (58.3%). The results of nuclear magnetic resonance (NMR, Bruker AV400MHz HD) analysis were as follows: Fig.19 shown.
[0160] 1 H NMR (C6D6, 25℃): 0.87(t,9H), 1.37(q,4H), 2.01(q,2H), 2.12(s,6H), 2.96(q,4H), 6.0(dt,8H).
[0161] The result of the analysis of the yellow liquid by thermogravimetric analysis (TGA, TA instrument company SDT Q600) at a nitrogen flow rate of 200 ml / min and a temperature rise rate of 10°C / min was 1.6%, with almost no residual mass. The results are shown as the thermogravimetric analysis (TGA) analysis results showing the weight loss percentage according to the temperature change. Fig. 20 shown.
[0162] [Synthesis Example 15] Synthesis of bis(ethylcyclopentadienyl)scandium chloride [(EtCp)2ScCl]
[0163] 264.4 ml (0.661 mol) of n-butyl lithium (n-BuLi) hexane solution (2.5 M) was slowly added to 300 ml of tetrahydrofuran (THF) and 66.09 g (0.661 mol) of ethylcyclopentadiene solution at -78 ° C and stirred for 30 minutes, and then stirred for 2 hours after heating to room temperature to produce a Li-EtCp solution. 50.0 g (0.330 mol) of scandium chloride and 150 ml of toluene were added to a new flask and cooled to -78 ° C while stirring. The previously produced Li-EtCp solution was slowly added to the flask containing the scandium chloride mixture and stirred at -78 ° C for 30 minutes, then heated to room temperature and stirred for 12 hours to synthesize bis (ethylcyclopentadienyl) scandium chloride.
[0164] [Synthesis Example 16] Synthesis of bis(ethylcyclopentadienyl)(diethyl-n-propionamidyl)scandium [(EtCp)2Sc(Et2nPr-AMD)]
[0165] After adding 47.01 g (0.330 mol) of diethyl-n-propionamide to 300 ml of tetrahydrofuran (THF) and cooling to -78°C, 132.2 ml (0.330 mol) of n-butyl lithium (n-BuLi) hexane solution (2.5 M) was slowly added dropwise to produce Li-(Et2nPr-AMD). The solution was stirred at -78°C for 30 minutes and then heated to room temperature, followed by additional stirring at room temperature for 2 hours. The produced Li-(Et2nPr-AMD) solution was slowly added dropwise to a flask containing (EtCp)2ScCl at room temperature and stirred at room temperature for 12 hours. The mixture was evaporated under vacuum, then filtered after being dissolved in 250 ml of pentane, and then the solvent and volatile substances were evaporated under vacuum. A colorless liquid was obtained by distilling the generated red liquid at 150°C and 28.4 mTorr. The yield was 73.33 g (59.6%).
[0166] 1 H NMR(C6D6,25℃):0.22(t,3H),1.00(t,6H),1.19(t,6H),1.33(q,2H),1.92(q,2H),2.38(q,4H),3.03(q,4H),6.0(dt,8H).
[0167] The results of the analysis of the pale yellow liquid sample by thermogravimetric analysis (TGA) at a nitrogen flow rate of 200 ml / min and a temperature rise rate of 10°C / min showed that there was 1.2% of the mass remaining. The results are shown as the thermogravimetric analysis (TGA) analysis results showing the weight loss percentage according to the temperature change. Fig.21 shown.
[0168] Thermogravimetric analysis (TGA) analysis results measured on the precursors according to Synthesis Examples 1 to 16 are shown in Table 1.
[0169]
Table 1
[0170] <![CDATA[TGA 1 / 2 (℃)]]> <![CDATA[TGA 1 / 2 (℃)]]> Synthesis example 2 230 Synthesis example 10 239 Synthesis example 3 252 Synthesis example 12 222 Synthesis example 4 250 Synthesis example 13 242 Synthesis example 6 235 Synthesis Example 14 243 Synthesis example 8 221 Synthesis Example 15 255 Synthesis example 9 228
[0171] Table 2 shows the results of thermogravimetric analysis (DSC) of the precursors according to Synthesis Examples 1 to 16.
[0172]
Table 2
[0173] Synthesis example 2 Synthesis example 8 Synthesis example 10 Synthesis example 12 Synthesis example 13 DSC(℃) 431 402 410 400 410
[0174] In order to confirm the viscosity of the precursors of Synthesis Examples 2 and 3, the samples were placed in the measuring container of a rotational viscometer (LVD2T manufactured by Brookfield) and the viscosity was measured at 25°C using a low viscosity rotor. The results are shown in Table 3.
[0175]
Table 3
[0176] Synthesis example 2 Synthesis example 3 Viscosity(cPs) 30 28
[0177] A thin film forming process was carried out using the precursor as described below.
[0178] The film formation evaluation by the atomic layer deposition process was carried out by bubbling method using the precursor of Synthesis Example 3 and O3 as an oxidant. The film formation evaluation used the change in film thickness according to the number of process cycles (Number of cycles vs. Thickness) as an indicator.
[0179] After the precursor of Synthesis Example 3 is heated to a vaporization temperature, argon (Ar) gas is injected through a dip line to generate bubbles, thereby supplying the vapor of the precursor compound of the gas yellow stage into the reaction chamber by means of a carrier gas.
[0180] A SiO2 substrate and a TiN substrate were placed in the reaction chamber and a deposition evaluation was performed under the conditions of precursor (5 to 15 seconds) - purge (60 seconds) - oxidant (5 to 15 seconds) - purge (30 seconds) in order to confirm the change in film thickness according to the number of process cycles while maintaining the set temperature (180 to 320°C).
[0181] The purge process was performed using argon (Ar) gas at a flow rate of 700 sccm, and ozone (O3) as a reaction gas at a flow rate of 220 g / m 3 The precursor was heated to 80°C, and the injection rate of argon carrier gas was 200 sccm. The number of processes was 50, 100 and 150. The film thickness change results according to the number of deposition cycles at different process temperatures (180°C, 220°C, 260°C, 275°C, 320°C) are shown in Figure 2. Fig. 22 shown.
[0182] pass Fig. 22 As a result, a certain film thickness variation according to the number of deposition cycles was observed for all the process temperature conditions for the evaluated SiO2 and TiN coupons.
[0183] The deposition rates at different temperatures are shown in Table 4.
[0184]
Table 4
[0185]
[0186] In addition, in order to confirm the change in low-temperature thin film deposition rate (ALD window) according to the process temperature, after the precursor according to the synthesis example 3 is heated to the vaporization temperature, argon (Ar) gas is injected through the production line (DIP line) to generate bubbles, so that the vapor of the precursor compound of the gaseous phase is supplied to the interior of the reaction chamber with the help of a transport gas.
[0187] SiO2 and TiN substrates were placed in the reaction chamber and supplied in the order of precursor (10 seconds)-purge (60 seconds)-oxidant (10 seconds)-purge (30 seconds) in order to confirm the change in film deposition rate according to the process temperature while changing the temperature. Argon (Ar) gas was supplied at a flow rate of 70 sccm as the purge gas. As the reaction gas, 220 g / m 3 Ozone (O3) was injected at a concentration of 1.5 %. The precursor was heated to 80°C, and the injection rate of argon carrier gas was 200 sccm. The number of processes was 50. The film deposition rate changes according to the process temperature are shown in the following figure. Fig.23 shown.
[0188] like Fig.23The results showed that similar film deposition rates (nm / cycle) were obtained at different engineering temperatures (180°C, 220°C, 260°C, 275°C, and 320°C), which confirmed that the ALD process has an engineering temperature range (ALD window).
[0189] In addition, in order to confirm the crystallinity of the thin film at different process temperatures, X-ray diffraction (XRD) analysis was performed on the Y2O3 thin films obtained at different temperatures in the SiO2 and TiN test pieces through the process evaluation, thereby confirming the crystallinity of the thin film. The crystallinity was measured after the deposition process, and the test pieces were also analyzed after heat treatment using rapid thermal annealing (RTA) at 600°C, 20 seconds and N2 conditions. The analysis results confirmed that for the thin film just after deposition, cubic Y2O3 crystallinity was observed in the thin film deposited under conditions above 300°C, while cubic Y2O3 crystallinity was observed under all temperature conditions after the heat treatment. The analyzed X-ray diffraction (XRD) results are as follows: Fig.24 shown.
[0190] In addition, X-ray electron spectroscopy depth analysis (XPS depth profile) was performed to confirm the composition and impurities of the film. For the Y2O3 film deposited at 275°C in the SiO2 and TiN test pieces, the composition and impurity content of the film were confirmed by X-ray electron spectroscopy (XPS) analysis. It was observed that the C and N impurities in the film were both 0%, and the O / Y content ratio was observed to have a composition ratio of 1.22. The results of the analyzed X-ray electron spectroscopy depth analysis (XPS depth profile) are as follows Fig.25 shown.
[0191] The present invention has been described with reference to preferred embodiments in the above content, but the present invention is not limited to the embodiments, and a person having general knowledge in the technical field to which the present invention belongs can make various modifications and changes to the present invention without departing from the gist of the present invention. These modifications and changes should be understood to be included in the scope of the claims attached to the present invention.
Claims
1. A precursor for forming a thin film containing yttrium or scandium, characterized in that: The invention comprises a yttrium or scandium compound represented by the following chemical formula 1: 【Chemical formula 1】 In the chemical formula 1, M is yttrium (Y) or scandium (Sc) metal, R1 and R3 are each independently a C1-C5 straight chain, branched or cyclic alkyl or alkenyl group, R2 is a hydrogen atom or a C1-C4 straight chain, branched or cyclic alkyl or alkenyl group, R' is the same as or different from each other and is a hydrogen atom or a C1-C4 straight chain, branched or cyclic alkyl or alkenyl group, and n is an integer from 1 to 5.
2. The yttrium- or scandium-containing thin film forming precursor according to claim 1, characterized in that: In the chemical formula 1, R2 is a C2-C4 linear, branched or cyclic alkyl or alkenyl group.
3. The yttrium- or scandium-containing thin film forming precursor according to claim 1, characterized in that: In the chemical formula 1, R1 and R3 are each independently a C2-C5 straight chain, branched chain or cyclic alkyl or alkenyl group, and R2 is a C2-C4 straight chain, branched chain or cyclic alkyl or alkenyl group.
4. The yttrium- or scandium-containing thin film forming precursor according to claim 1, characterized in that: In the chemical formula 1, R1 and R3 are methyl groups.
5. The yttrium- or scandium-containing thin film forming precursor according to claim 1, characterized in that: In the chemical formula 1, the R2 is an isopropyl group.
6. The yttrium- or scandium-containing thin film forming precursor according to claim 1, characterized in that: In the chemical formula 1, R1 and R3 are each independently a C1-C5 straight-chain alkyl or alkenyl group.
7. The yttrium- or scandium-containing thin film forming precursor according to claim 1, characterized in that: In the chemical formula 1, R1 and R3 are each independently a C1-C5 straight-chain alkyl or alkenyl group, and R2 is a C1-C4 straight-chain alkyl or alkenyl group.
8. The yttrium- or scandium-containing thin film forming precursor according to claim 1, characterized in that: In the chemical formula 1, R1 and R3 are all the same and are C1-C5 linear, branched or cyclic alkyl or alkenyl groups.
9. The yttrium- or scandium-containing thin film forming precursor according to claim 1, characterized in that: In the chemical formula 1, all of R1 to R3 are the same and are C1-C4 linear, branched or cyclic alkyl or alkenyl groups.
10. The yttrium- or scandium-containing thin film forming precursor according to claim 1, characterized in that: The viscosity of the yttrium- or scandium-containing thin film-forming precursor is 60 cP or less.
11. The yttrium- or scandium-containing thin film forming precursor according to claim 1, characterized in that: The melting point of the yttrium- or scandium-containing thin film forming precursor is 70° C. or less.
12. The yttrium- or scandium-containing thin film forming precursor according to claim 1, characterized in that: The thin film forming precursor additionally contains a solvent.
13. The yttrium- or scandium-containing thin film forming precursor according to claim 12, characterized in that: The solvent is C1-C 16 One or more of saturated or unsaturated hydrocarbons, ketones, ethers, glycol dimethyl ether, esters, tetrahydrofuran and tertiary amines.
14. The yttrium- or scandium-containing thin film forming precursor according to claim 12, characterized in that: The solvent is contained in an amount of 1 to 99% by weight relative to the total weight of the thin film forming precursor.
15. The yttrium- or scandium-containing thin film forming precursor according to claim 1, characterized in that: The thin film forming precursor is at least one selected from the group consisting of the following structures:
16. A method for forming a thin film containing yttrium or scandium, characterized in that: The method comprises the step of forming a thin film on a substrate using the thin film forming precursor according to claim 1 or claim 12.
17. The method for forming a thin film containing yttrium or scandium according to claim 16, characterized in that: The process of forming a thin film on a substrate comprises: a process of forming a precursor thin film by depositing the thin film forming precursor on the surface of a substrate; and The process of reacting the precursor film with a reactive gas.
18. The method for forming a thin film containing yttrium or scandium according to claim 17, characterized in that: The step of forming a precursor thin film includes a step of vaporizing the thin film forming precursor and transferring the vaporized precursor into a chamber.
19. The method for forming a thin film containing yttrium or scandium according to claim 17, characterized in that: The deposition is performed by one of a dielectric spin coating (spin-on dielectric, SOD) project, a low temperature plasma (Low Temperatur e Plasma, LTP) project, a chemical vapor deposition (Chemical Vapor Deposition, CVD), a plasma chemical vapor deposition (Plasma Enhanced Chemical Vapor Deposition, PECVD), a high density plasma chemical vapor deposition (High Density Plasma-Chemical Vapor Deposition, HDPCVD) project, an atomic layer deposition (Atomi c Layer Deposition, ALD) project or a plasma atomic layer deposition (Plasma-Enhanced Atomi c Layer Deposition, PEALD) project.
20. The method for forming a thin film containing yttrium or scandium according to claim 16, characterized in that: The process of forming a thin film on a substrate comprises: A step of forming a thin film by supplying the thin film forming precursor to a substrate and applying plasma.
21. A semiconductor component, characterized in that: A thin film containing yttrium or scandium produced by the thin film forming method according to claim 16.
Citation Information
Patent Citations
Preparation of lanthanide-containing precursors and deposition of lanthanide-containing films
KR101660052B1
Lanthanum precursors for depositing lanthanum, lanthanum oxide, and lanthanum nitride films.
KR1020190008427A
Lanthanum compound and methods of forming thin film and integrated circuit device
KR1020190109142A
Yttrium / lanthanide-containing precursor compounds, precursor compositions including the same for forming films, and method of forming yttrium / lanthanide-containing films using the precursor composition
KR1020210084297A
Yttrium compound, forming method of thin film comprising the same, and semiconductor substrate preapared thereby
KR1020210089015A